The uneven transition towards universal literacy in Spain, 1860-1930 - Francisco J. Beltrán Tapia; Alfonso Díez-Minguela; Julio Martínez-Galarraga; Daniel A. Tirado (European Historical Economics Society (EHES), 2019)
This study provides new evidence on the advance of literacy in Spain during the period 1860-1930. A novel dataset, built with historical information (over 8,000 municipalities) from the Spanish population censuses, enables us to describe this process in detail from the end of the Ancien Régime to the Second Republic. The study thus presents stylized facts at a very low level of geographic aggregation, thereby permitting a closer examination of the main patterns. Overall, spatial differences in literacy were sizeable during the whole nineteenth century. Furthermore, these disparities were only significantly reduced between 1900 and 1930 when the growing demand for these basic skills were met by a stronger government intervention.
Keywords: I20; N33; N93; O15; 330; Literacy; Regional Disparities; Nineteenth Century; Spain